Horch - Sense, Torsten 1961- (Fotopoulos Filmproduktion, 2007)
A group of young cineastes. Their dream to make their own film. The constant rejections by various funding bodies. A break-in into the Babelsberg Film Studios. The shoot that has to be completed in one night. A film about a friend who is falsely accused of murder, and a film about an angel who wants to save and protect him. Then the fear of being caught. The reporters of the press who dis-cover them. The police, who catch them in the end. The real murderer. The real murderer? And somebody, who could help them, but who is not understood. [Movie Database, written by Giorgis Fotopoulos]
Bildformat 16:9 (1.66:1)
Orig.: Deutschland, Griechenland 2007
Enth. Setbilder